Response Of Indonesian Government Bond Yield To The Volatility Of United States Government Bond Yield - Hutabarat, Arnold Sultantio; Damanik, Darwin; Listari, Sinta (Program Vokasi dan LPPM IBI Kesatuan, 2025)
This study was conducted to investigate the extent to which the Indonesian exchange rate, inflation, and government bond yields affect the volatility of US government bond yields. Using quantitative inferential methods, this study attempts to analyze the causal relationship between the independent and dependent variables. The data used are derived from secondary sources, namely data on the Rupiah exchange rate, Indonesian inflation, historical data on Indonesian Government Securities (SUN), and US Treasury Notes, covering the period from 2015 to 2024. The data collection process was carried out through documentation techniques, ensuring the validity and reliability of the information obtained. In the analysis stage, the data were processed using E-Views statistical analysis, which involved a series of tests. These included descriptive statistical tests to provide an overview of the data, classical assumption tests to ensure the statistical model met the requirements, and hypothesis tests to verify initial assumptions. Based on the comprehensive analysis, the findings of this study consistently indicate that inflation has a positive and significant effect on the volatility of US bond yields. However, the Rupiah exchange rate and Indonesian bond yields did not have a significant effect on the volatility of US bond yields. Keywords: Bond Yields; Volatility; Indonesia Government Bond; United States Government Bond.